Buddhist sculpture by stone and wood material in south vietnam from the first to 7th century: Through some cases - Van Lac, VO (Opción, 2020)
The Article investigated, studied the items related to sculpture of Phu Nan, which existed from the 1st to 7th century Anno Domini of Christian era. Through Buddha statues in wood and stone materials, they clearly show the artistic style influenced by 3rd century AD Gandhara, and India’s classic Gupta style. These are two artistic styles which formed very early in India. Excavated and Found typical Buddha statues in some archaeological sites currently display at the Ho Chi Minh City Museum of Fine Arts history. From these statues we can see the interference of Buddhist influence in India in South Vietnam.